Respuesta :

Answer:

4x-1

Step-by-step explanation:

The working is shown in the above photo

Ver imagen nish11235

Answer:

see explanation

Step-by-step explanation:

Given f(x) then the derivative f'(x) is

f'(x) = lim ( h tends to zero ) [tex]\frac{f(x+h)-f(x)}{h}[/tex]

      = lim ( h to 0 ) [tex]\frac{2(x+h)^2-(x+h)-(2x^2-x)}{h}[/tex]

     = lim ( h to zero ) [tex]\frac{2(x^2+2hx+2h^2)-x-h-2x^2+x}{h}[/tex]

     = lim ( h to zero ) [tex]\frac{2x^2+4hx+2h^2-h-2x^2}{h}[/tex]

     = ( lim h to 0 ) [tex]\frac{4hx+2h^2-h}{h}[/tex]

     = ( lim h to 0 ) [tex]\frac{2h(2x+h)-h}{h}[/tex]

     = lim ( h to 0 ) [tex]\frac{2h(2x+h)}{h}[/tex] - [tex]\frac{h}{h}[/tex] ← cancel h on numerator/ denominator of both

     = lim( h to 0 ) 2(2x + h) - 1 ← let h go to zero

f'(x) = 4x - 1